The Influence of Carbon Fiber Content on the Tensile, Flexural, and Thermal Properties of the Sisal/PMMA Composites - Harini, Sosiati; Yuniar, N.D.M; Saputra, D.; Sinin, Hamdan (Joint Journal of Novel Carbon Resource Sciences and Green Asia Strategy, 2022)
The polymethyl-methacrylate (PMMA)-based composites have been developed for denture-based materials. Sisal/PMMA and sisal/carbon/PMMA composites are a good choice for denture-based materials. Therefore, the different properties are presently studied to explore the effect of carbon fiber content on the tensile, flexural, and thermal properties of untreated sisal (US)/treated carbon (TC)/PMMA composites. The composites were made by hand lay-up and cold press with 20% fiber loading and different US/TC ratios of 2:1, 1:1, and 1:2. The carbon fiber was treated by soaking it in a solution of 68% HNO3 for various durations from 24 to 96 hours. The scanning electron microscopy (SEM) results revealed an excellent bonding strength between the fibers and the matrix and a high degree of fiber dispersion in the matrix. These phenomena led to the composites with a 1:2 US/TC ratio reaching the maximum tensile strength (57.70 ± 6.15 MPa) and flexural strength (108 ± 6.61 MPa). The mechanical properties of the composites improved by adding carbon fiber to the sisal/PMMA composite. The thermogravimetric (TGA) analysis indicated that the thermal stability of the US/TC/PMMA composites increases by the addition of carbon fiber.